2011
DOI: 10.3748/wjg.v17.i13.1753
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux in cirrhotic patients without esophageal varices

Abstract: Cirrhotic patients without EV presented esophageal motor disorders and mixed acid and bile reflux was the main pattern; the cirrhosis itself was an important causative factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In patients with cirrhosis and portal hypertension, gastroesophageal reflux occurs at a high frequency (64%) . A study including 78 cirrhotic patients without esophageal varices confirmed by upper gastroesophageal endoscopy revealed that the incidence of abnormal reflux and reflux esophagitis was 55.13% and 37.18%, respectively . In the present study, 77.88% of cirrhotic patients experienced one or more disturbing GI symptoms, with bloating being the most frequent symptom (prevalence rate, 40.38%).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In patients with cirrhosis and portal hypertension, gastroesophageal reflux occurs at a high frequency (64%) . A study including 78 cirrhotic patients without esophageal varices confirmed by upper gastroesophageal endoscopy revealed that the incidence of abnormal reflux and reflux esophagitis was 55.13% and 37.18%, respectively . In the present study, 77.88% of cirrhotic patients experienced one or more disturbing GI symptoms, with bloating being the most frequent symptom (prevalence rate, 40.38%).…”
Section: Discussionsupporting
confidence: 48%
“…In patients with cirrhosis and portal hypertension, gastroesophageal reflux occurs at a high frequency (64%). 29 A study including 78 cirrhotic patients 30 In the present study, 77.88% of cirrhotic patients experienced one or more disturbing GI symptoms, with bloating being the most frequent symptom (prevalence rate, 40.38%). The prevalence rate recorded in our study is similar to that reported by Fritz and Hammer.…”
Section: Risk Factors Of Depression and Anxiety In Cirrhosis E67mentioning
confidence: 55%
“…Of all patients in the study with ascites, 31.9% (36/ [11][12][13][14][15][16][17][18] for PPI nonusers, P = 0.06). Further investigation of the association between PPI use and increased risk of SBP development showed that PPI use increased the risk of SBP development only in patients who did not have a previous SBP episode (n = 84) ( Fig.…”
Section: Risk Factors Of Spontaneous Bacterial Peritonitismentioning
confidence: 99%
“…Several clinical trials demonstrated no improvement in the risk of portal hypertension-related bleeding with PPI treatment [11,12]. Another problem is that although in some studies GERD was more common in patients with cirrhosis as compared with a healthy population, the low sample size of these studies makes their results highly questionable [13,14]. Regardless of these uncertainties, PPIs are frequently prescribed for patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of GERD in liver cirrhosis patients was reported to be ranging between 55%-64%[ 13 , 14 ]. Zhang et al [ 13 ] assessed 78 cirrhotic patients without EV using esophageal manometry, simultaneous ambulatory 24-h esophageal pH, and bilirubin monitoring and esophagogastric duodenal endoscopy (EGD). The study showed that the resting LES pressure in cirrhotic patients was diminished.…”
Section: Liver Cirrhosis and Gerdmentioning
confidence: 99%